Risk of Debt-Based Financing in Indonesian Islamic Banking - Kharisya Ayu Effendi (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2017)
The purpose of this study is to know the risk of debt-based financing in Islamic banking in Indonesia by using an accounting based calculation, those are NPF analysis, Credit risk Z-score and Altman Z-score. This study is telling about the risk of debt-based finacing on Indonesian Islamic banking using an accounting based measurement, those are NPF analysis, Credit Risk Z-score analysis and Altman Z-score analysis. The data was obtained from 2011 to 2015 from the website of each bank. The result is a risk on debt-based financing on Indonesian Islamic banking is low. The measurement using 3 accounting based measurement tool gives a consistent result, that is Indonesian Islamic banking use a debt-based financing have a high financial stability and a low risk.DOI: 10.15408/aiq.v9i2.4821